Stereoselective Formation of (E)-β-Alkoxy Acrylates from Fischer Carbene Complexes and Chelated Amino Acid Ester Enolates - Chaudhuri, Rupsha; Kazmaier, Uli (Synlett, 2014)
Chelated amino acid ester enolates react with alkyl Fischer carbene complexes via nucleophilic attack on the electrophilic carbene center. Subsequent elimination of the metal fragment and trifluoroacetamide results in the formation of β-alkoxy-α,β-unsaturated esters in a highly E-stereoselective fashion.
Keywords: acrylates; amino acids; carbene complexes; enolates; Fischer carbenes; α,β-unsaturated esters